The effect of physical activity on thiamin, riboflavin and vitamin B6 requirements - Manore, M. M. (1996)
Exercise increases both energy and protein needs and, thus, also increases the total daily needs of thiamin, riboflavin, and vitamin B6 in active individuals. However, the RDAs for these nutrients are already linked to energy and protein intakes. Thus, ideally dietary intakes of these vitamins by active individuals should be adequate unless dietary food choices are poor or energy intake is restricted. No extensive research has been done on whether nutrient requirements are higher in active individuals with chronic diseases, energy restriction, musculoskeletal injuries, or individuals under high stress.